The role of Herpes simplex virus type 1 and 2 in patients with neurodegenerative diseases - Hassan, Mohamad I.; Aboud, Rana S.; Al-Ahmer, Saife D. (Iraqi Journal of Science, 2018)
With the growing number of patient’s being diagnosed with Parkinson’s disease and Multiple Sclerosis each year it is becoming ever more important to find the cause for these neurological disorders. The present study attempts to shed light on one of the factors that may play a role as a causative agent in these neurological diseases by finding a correlation between the Herpes simplex virus type 1 and 2 in patients with Parkinson’s disease and multiple sclerosis by detecting the virus in these patients using immunological techniques. Sixty patients with neurological diseases (40 patients with Multiple sclerosis and 20 patients with Parkinson’s disease) who’s ages ranged from (17-76) years have been investigated. Samples were collected during the time period between November 2017 and April 2018 and compared to twenty five apparently healthy individuals as a control group. All the studied groups were measured for herpes simplex virus type-1 IgM and herpes simplex virus type-2 IgM by using the enzyme linked immuno sorbent assay. The results of the present study showed that there was a highly significant difference (p<0.01) in the concentration of IgM HSV-1 and HSV-2 in the sera of patients with MS and PD compared to the control group, While there was a none-significant difference (p>0.05) in the concentration of IgM HSV-1 and HSV-2 according to the gender. Thus, there is a likely possibility the HSV could be a contributing factor in the activation of some neurological diseases by the means of initiating an autoimmune reaction against the host’s nerve cells. The nerve cells have proteins that resemble portions of the virus from a structural and genetic stand point.